Monotonic tests on masonry elements with different angles of inclination of the bed joints under uniaxial compression. (3rd June 2019) - Weber, Marius; Sharma, Akanshu; Hofmann, Jan
This paper describes the results from monotonic tests performed on masonry elements with different angles of inclination of the bed joints relative to the horizontal under uniaxial compression. Two different types of bricks (calcium-silicate and clay bricks) were tested under uniaxial compression stress state. The main test parameter was the angle of inclination of the bed joints, which was varied between 0 and 90 degrees in the interval of 15 degrees. The tests were performed in displacement control in order to capture the post-peak response of the masonry elements as well. The applied displacements were increased monotonically. During the tests, main measurements were performed to measure the edge deformation, detection of strain on the masonry surface using a photogrammetric method, and documentation of the crack propagation and fracture behaviour. The strength and the stiffness properties, as well as stress-strain relationships as a function of the angle of inclination of the bed joints and the comparison between the principle directions of stresses and strains is reported here.